222k views
0 votes
See attached picture

See attached picture-example-1
User Heldt
by
6.1k points

1 Answer

6 votes

Answer:


(f(x+h)-f(x))/(h)
=2x - h

Explanation:

Given


f(x) = 8 - x^2

Required

Determine:
(f(x+h)-f(x))/(h)

First, we calculate f(x + h)


f(x) = 8 - x^2


f(x+h) = 8 - (x+h)^2


f(x+h) =8- x^2-2xh-h^2

So, we have:


(f(x+h)-f(x))/(h)
= (8- x^2-2xh-h^2 - 8 + x^2)/(h)


(f(x+h)-f(x))/(h)
= (8 - 8 + x^2- x^2-2xh-h^2)/(h)


(f(x+h)-f(x))/(h)
= (-2xh-h^2)/(h)


(f(x+h)-f(x))/(h)
=2x - h

User Khaan
by
6.5k points